2020
DOI: 10.1186/s12882-020-02082-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and methods of the prevalence and pharmacogenomics of tenofovir nephrotoxicity in HIV-positive adults in south-western Nigeria study

Abstract: Background Individuals of African descent are at higher risk of developing kidney disease than their European counterparts, and HIV infection is associated with increased risk of nephropathy. Despite a safe renal profile in the clinical trials, long-term use of tenofovir disoproxil fumarate (TDF) has been associated with proximal renal tubulopathy although the underlying mechanisms remain undetermined. We aim to establish the prevalence of and risk factors for TDF-induced kidney tubular dysfunction (KTD) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, efforts are being made to implement pharmacogenomics-guided treatment in Nigeria. Currently, pharmacogenomics testing is being used to evaluate the prevalence of genetic polymorphism among people living with Human Immunodeficiency Virus (HIV) who are receiving highly active antiretroviral therapy [ 18 , 19 ]. The findings from these ongoing studies are expected to guide the implementation of pharmacogenomics services into patient care.…”
Section: Introductionmentioning
confidence: 99%
“…However, efforts are being made to implement pharmacogenomics-guided treatment in Nigeria. Currently, pharmacogenomics testing is being used to evaluate the prevalence of genetic polymorphism among people living with Human Immunodeficiency Virus (HIV) who are receiving highly active antiretroviral therapy [ 18 , 19 ]. The findings from these ongoing studies are expected to guide the implementation of pharmacogenomics services into patient care.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an equipoise on the safety pro le of TDF, following the emergence of case series and studies that report features of RTD among patients on TDF. (7,8,(16)(17)(18)(19)(20)(21)(22)(23)(24)34). Histological renal changes associated with TDF are not uncommon (36).…”
Section: Discussionmentioning
confidence: 99%
“…TDF mainly affects the proximal renal tubule, and studies have reported the presence of tubular proteinuria, urinary phosphate wasting and other parameters of renal tubular dysfunction resembling the Fanconi syndrome in PLHIV taking TDF-containing regimens (6, [17][18][19][20][21][22][23][24]. TDF renal toxicity occurs as early as 3 to 6 months (25) and is thought to have the spontaneous resolution in 24 months (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apical membrane transporters multidrug resistance protein (MRP-4) and MRP-2 then release the drug into the tubular lumen. (Multidrug resistance proteins, encoded by ATP-binding cassette transporter sub-family C member (ABCC4) and ABCC2 genes [ 3 , 4 ]).…”
Section: Introductionmentioning
confidence: 99%